Monetary union among member countries of the Gulf Cooperation Council - Schaechter, Andrea; Fasano-Filho, Ugo, 1956- (Washington DC : International Monetary Fund, 2003)
This occasional paper examines the common code of fiscal conduct, institutional requirements, and structural policies, needed for a successful monetary union among the GCC countries.
Includes bibliographical references (p. 58-60).
nmn 3/06/13
Loans
Keywords: Gulf Cooperation Council; Monetary unions -- Persian Gulf Region; Persian Gulf Region -- Economic integration